2021
DOI: 10.1101/2021.06.16.448727
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate Protein Function Prediction via Graph Attention Networks with Predicted Structure Information

Abstract: Experimental protein function annotation does not scale with the fast-growing sequence databases. Only a tiny fraction (<0.1%) of protein sequences in UniProtKB has experimentally determined functional annotations. Computational methods may predict protein function in a high-throughput way, but its accuracy is not very satisfactory. Based upon recent breakthroughs in protein structure prediction and protein language models, we develop GAT-GO, a graph attention network (GAT) method that may substantially imp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…We have developed NetGO 3.0 to improve the performance of large-scale AFP by incorporating a new component LR-ESM, which utilizes a protein language model to generate powerful representations of proteins. Interesting future work would be integrating protein structural information into NetGO to enhance the performance of AFP [18][19][20]. Each GO term is attached with tags, which illustrates that the GO term is predicted correctly by corresponding methods.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed NetGO 3.0 to improve the performance of large-scale AFP by incorporating a new component LR-ESM, which utilizes a protein language model to generate powerful representations of proteins. Interesting future work would be integrating protein structural information into NetGO to enhance the performance of AFP [18][19][20]. Each GO term is attached with tags, which illustrates that the GO term is predicted correctly by corresponding methods.…”
Section: Discussionmentioning
confidence: 99%
“…Graph convolutional networks apply spectral convolution in the graph Fourier domain to aggregate neighboring representations for feature learning 32 . They have been used for protein structure refinement 33 and protein function prediction 34 . These attempts to encode protein context information make the prediction of mutation induced stability changes possible, yet it is still scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…32 They have been used for protein structure refinement 33 and protein function prediction. 34 These attempts to encode protein context information make the prediction of mutation induced stability changes possible, yet it is still scarcely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As protein function is jointly determined by its 3-dimensional confor-mation and primary amino acid sequence (Mitchell et al 2019; Dawson et al 2017) this suggests that functional effects of mutations should be modeled jointly as well. It has been shown that protein structure information can be used to predict its function (Gligorijevic et al 2021; Lai and Xu 2022). Although the most successful existing methods for protein mutation effect prediction rely on sequence and evolutionary information (Meier et al 2021; Hopf et al 2017; Riesselman et al 2018), we hypothesized that a generative model, conditioned solely on structure and partial sequence, could be used as a zero-shot predictor for functional effects on single point mutations.…”
Section: Introductionmentioning
confidence: 99%